The Relationship between the Use Of 3-Month Injectable Contraceptives and Weight Gain at Berkah House of Midwife Katmi Bekasi District in 2022 - Melinda Nestami; Olivia Nency (Jurnal EduHealth, 2023)
The most popular hormonal contraceptive in West Java is 3-month injectable birth control. with the most common side effect experienced is weight gain as much as 61.2% of all acceptors. The purpose of this study was to determine the relationship between the use of 3-month injectable contraceptives and weight gain at Berkah House of Midwife Katmi, Bekasi Regency in 2022. This research design is an analytic survey with a retrospective cross sectional approach. The study population was the total number of re-visiting 3-month injectable family planning acceptors, namely 130 people, with the sampling technique using the total population with the chi-square test analysis. Results; It was found that 3-month injectable contraceptive acceptors who experienced weight gain were 61 people (47%) of the total. Based on the Chi-square test results obtained a value of P = 1 > α = 0.05. It can be concluded that there is no relationship between the use of 3-month injectable contraceptives and maternal weight gain at Berkah House of Midwife Katmi, Bekasi Regency in 2022. It is hoped that midwives can increase knowledge and conduct further research on this research.